FABRICATION OF PVA/TiO2 NANOFIBERS BY ELECTROSPINNING METHOD AS PHOTOCATALYTIC DEGRADATIO - Aulia Aska Mei, Sisy Anggelina; Hari Kusumawati, Diah (Indonesian Physical Review, 2022)
The nanofiber fabrication process was optimized to determine the effect of stress variations on the morphology and diameter of the nanofibers produced for the absorption of methylene blue dye in water. PVA/TiO2 nanofibers were made using the electrospinning method. The nanofiber fabrication process begins by dissolving 10% PVA with the addition of 0.05 g of TiO2 nanoparticles, the collector tip distance is 15 cm with varying voltages of 12, 15, and 18 kV. PVA/TiO2 nanofiber characterization was carried out using FTIR, SEM, EDS, and UV-Vis Spectrophotometer. The results showed success in forming PVA/TiO2 nanofibers. The nanofibers show a fibrous structures with a diameter of 252 nm for PVA and 237 nm for PVA/TiO2 with a uniform surface and contained TiO2 nanoparticles scattered within the nanofibers. The photocatalytic testing within 5 hours shows that PVA nanofibers can degrade up to 39.29% of the methylene blue dye, while TiO2 powder is up to 55.48%. Hence, the PVA/TiO2 nanofibers can degrade the dye up to 97.02%. The results of good transparency on the UV-Vis Spectrophotometer test are shown in the visible light region caused by the uniform distribution of TiO2 nanoparticles in the nanofiber.